Defect Analysis of ZA Fertilizer Products with Fault Tree Analysis (FTA) and Failure Mode Effect Analysis (FMEA) Methods at PT. XYZ - Nuridati, Hawari; Rochmoeljati, Rr. (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2023)
PT XYZ is one of the fertilizer producers in Indonesia. The problem that often occurs in the company is that there are product defects that cause the production process to be ineffective.  One of the products that has a high percentage of defects is non-subsidized ZA fertilizer. Research using Fault Tree Analysis (FTA) and  Failure Mode and Effect Analysis (FMEA) methods to find out the causes of rejects or rejects in products and can provide preventive solutions so that these defects do not occur. In this study, 4 types of defects were found, namely failed weighing with a chance of defect occurrence of 0.138%, mixed color defect with a chance of defect occurrence of 0.115%, crystal clumping defect with a chance of defect occurrence of 0.115%, and defect mixed with dirt with a chance of defect occurrence of 0.116%, mixed color, crystal clumping, and mixed with dirt. The root causes of these defects include less careful operators, hasty operators, operators do not check the fertilizer bag machine needs maintenance, machine trouble, operators do not check the level on the machine regularly, poor air circulation, lack of cleaning facilities, operators work not according to SOP, lack of supervision, lazy operators, no barrier with other fertilizers, lack of lighting.